PR activities of the banking sectors in Turkey (Herald of Journalism, 2018)
The author considers the research on Turkish banking sector problems in carrying out work related with PR. Explore different techniques of PR. Based on the theoretical and practical scientific works of Turkish experts, the author identifies the main directions of PR-activity in banking services. The role of the media in spreading this activity.Key words: PR, banking, finance, assets.